Mito Stress Assay of PBMCs With Seahorse XFe96 Flux Analyzer and Comparison of Poly-D-Lysine and Poly-L-Lysine for Cell Affinity - Kumudu Subasinghe; R. Berry III; Megan Rowe; Ali Winters; Shaohua Yang; Nicole Phillips (Bio-Protocol, 2025)
The Seahorse 96 XF Analyzer (Agilent Technologies, Santa Clara, CA, USA) has been an effective tool in non-invasively measuring mitochondrial function for the past decade. It is a high-throughput respirometer that is considered the “gold standard” for quantifying mitochondrial function and bioenergetics in cells. Peripheral blood mononuclear cells (PBMCs) play a selective role in immune system responses and are key components of human immunity. Recent studies have suggested that these cell populations provide an overview of systemic changes within the body and therefore provide a source of sensitive biomarkers. Assessing mitochondrial function in PBMCs has been shown to provide an indication of metabolic stress associated with diseases such as diabetes and neurodegenerative conditions such as Alzheimer’s disease. In this protocol, we use two adhesive compounds, Poly-D-Lysine (PDL) and Poly-L-Lysine (PLL), at 50 μg/mL each per well, to immobilize PBMCs to a specialized Seahorse microplate to perform mitochondrial stress assay using the Seahorse Analyzer. We compared six cell densities of PBMCs to identify the optimal cell density for use in Seahorse Mito Stress analysis. This protocol includes the immobilization of freshly isolated PBM cells into a Seahorse microplate, hydration and calibration of the sensor cartridge, cell seeding, running the Seahorse Analyzer for the Mito Stress test, and simple data analysis to compare the effectiveness of PLL and PDL as the coating agent for PBMCs. The data analysis indicates that there is no statistical difference between PLL and PDL.